Factors Produced by Macrophages Eliminating Apoptotic Cells Demonstrate Pro-Resolutive Properties and Terminate Ongoing Inflammation - Bonnefoy, Francis; Gauthier, Thierry; Vallion, Romain; Martin-Rodriguez, Omayra; Missey, Anais; Daoui, Anna; Valmary-Degano, Séverine; Saas, Philippe; Couturier, Mélanie; Perruche, Sylvain (Frontiers in Immunology, 2018)
Unresolved inflammation is a common feature in the pathogenesis of chronic inflammatory/autoimmune diseases. The factors produced by macrophages eliminating apoptotic cells during resolution are crucial to terminate inflammation, and for subsequent tissue healing. We demonstrated here that the factors produced by macrophages eliminating apoptotic cells were sufficient to reboot the resolution of inflammation in vivo, and thus definitively terminated ongoing chronic inflammation. These factors were called SuperMApo and revealed pro-resolutive properties and accelerated acute inflammation resolution, as attested by both increased phagocytic capacities of macrophages and enhanced thioglycollate-induced peritonitis resolution. Activated antigen-presenting cells exposed to SuperMApo accelerated their return to homeostasis and demonstrated pro-regulatory T cell properties. In mice with ongoing collagen-induced arthritis, SuperMApo injection resolved and definitively terminated chronic inflammation. The same pro-resolving properties were observed in human settings in addition to xenogeneic colitis and graft-vs.-host disease modulation, highlighting SuperMApo as a new therapeutic opportunity to circumvent inflammatory diseases.